Water consumption and yield efficiency of wheat plants treated with Trinexapac-ethyl - Turek, Thais Lemos; Michelon, Luiz Henrique; Tochetto, Cláudia; Coelho, Antônio Eduardo; Fioreze, Samuel Luiz (Revista de Ciências Agroveterinárias, 2018)
Efficient use of the resources of the growing environment, which is affected by plant traits, is very important for crop adaptation on production system. This work aimed to study the water consumption and yield efficiency of wheat plants treated with Trinexapac-ethyl. Two experiments were carried out, in greenhouse conditions, between 2014 and 2015. Experiments were arranged in randomized blocks design in a factorial 2x3, with four replicates. Two wheat cultivars were sprayed with three Trinexapac-ethyl doses (0, 125 and 188 g a.i. ha-1), at main culm elongation stage. The water consumption, plant height, source-sink distance and the morphological parameters of the flag leaf were evaluated. At the end of the growing cycle, yield and yield components were determined, as well as harvest index. Trinexapac-ethyl reduced plant growth, without affecting grain production. Plant growth regulator application does not reduce either water consumption or wheat crop harvest index.